EFFECT OF FENUGREEK ON THE LEVEL OF MALONE DIALDEHYDE AND CERTAIN HEMATOLOGIC PARAMETERS IN TUMOR-BEARING ANIMALS - V. V. Zhylenko; S. P. Zaletok (Сибирский онкологический журнал)
This paper deals with effect of fenugreek on the level of malone dialdehyde and certain hematologic parameters in animals with grafted Ca755 mammary carcinoma, L1210 lymphoid leukemia and Guerin carcinoma substrains, resistant to doxorubicin and cisplatin. Fenugreek consumption was shown to amend hematologic parameters and decrease level of malone dialdehyde in liver (32–63 %), kidney (21 %) and heart (33 %) in animals with different genesis tumors. Thus, these results show that fenugreek can be a potential antioxidant agent.